'Weird English from an American'? Folk engagements with language ideologies surrounding a self-help English language learning comic book published in Japan. Issue 1 (2nd January 2018) - Tajima, Misako
Abstract: This article reports on a study of how users of a self-help English language learning comic book published in Japan engage with various English-related ideologies through posting customer reviews on online bookstores. Analysis of the reviews demonstrates that these users occasionally celebrate, and at other times counter, dominant language ideologies, drawing on their own views about English, English language teaching, ideal English teachers, and native English speakers. By elucidating how the users struggle with prevalent language ideologies, the article argues that contrary to the traditional sociolinguistic belief that English is infrequently used among people in Japan, a country belonging to the Expanding Circle within the framework of World Englishes, they have active engagements with the language. The argument contributes to the review of the concept of language use, serving as a promising start for the reconsideration of the nation-state division over English based on the degree of English use.